Cognitive, Emotional and Psychological Manifestations in Amyotrophic Lateral Sclerosis at Baseline and Overtime: A Review - Benbrika, Soumia; Desgranges, Béatrice; Eustache, Francis; Viader, Fausto (Frontiers in Neuroscience, 2019)
It is now well recognized that, in addition to motor impairment, amyotrophic lateral sclerosis (ALS) may cause extra-motor clinical signs and symptoms. These can include the alteration of certain cognitive functions, impaired social cognition, and changes in the perception and processing of emotions. Where these extra-motor manifestations occur in ALS, they usually do so from disease onset. In about 10% of cases, the cognitive and behavioral changes meet the diagnostic criteria for frontotemporal dementia. The timecourse of behavioral and cognitive involvement in ALS is unclear. Whereas longitudinal studies have failed to show cognitive decline over time, some cross-sectional studies have demonstrated poorer cognitive performances in the advanced stages of the disease. Neuroimaging studies show that in ALS, extra-motor signs and symptoms are associated with specific brain lesions, but little is known about how they change over time. Finally, patients with ALS appear less depressed than might be expected, given the prognosis. Moreover, many patients achieve satisfactory psychosocial adjustment throughout the course of the disease, regardless of their degree of motor disability. There are scant longitudinal data on extra-motor impairment in ALS, and to our knowledge, no systematic review on this subject has yet been published. Even so, a better understanding of patients’ clinical trajectory is essential if they are to be provided with tailored care and given the best possible support. We therefore undertook to review the evidence for extra-motor changes and their time course in ALS, in both the cognitive, emotional and psychological domains, with a view to identifying mechanisms that may help these patients cope with their disease.